Strategy for Sustainable Halal Tourism Development in Perlang Village, Bangka Belitung Islands Province, Indonesia - Maftukhatusolikhah, Maftukhatusolikhah; Handayani, Disfa Lidian; Pratomo, Nardi; Iqbal, M.; Litriani, Erdah (Fakultas Syariah UINSI Samarinda, 2024)
In developing halal tourism, enhancing competitiveness must also address other important issues, such as environmental sustainability. After Covid-19, environmental issues increased along with the growth of halal tourism. Consequently, it is essential to implement effective strategies for developing halal tourism. Perlang is one of the villages that has succeeded in turning former mining land into a tourist attraction, and is recognized as one of the 50 best tourist attractions in Indonesia. This research aims to see how specific strategies have been used in developing a tourist village with the concept of sustainable halal tourism. It also looks at how the strategy model is effectively utilized to realize a tourist village concept that carries halal and sustainable values. It employs a qualitative method with a case study of Perlang Village by exploring documentation, observation, interviews, and Focus Group Discussions. The results showed that the Sustainable and Responsible Halal Tourism development model in Perlang fulfills the indicators that make it attractive, authentic, and consistent with halal principles, aligned with achieving sustainable development goals. The benefits of this tourist destination can be felt by the wider community inclusively and future generations.